AIMS AND OBJECTS OF STATE AUTOMOTIVE INDUSTRY CONTROL AND WAYS OF IMPROVEMENT OF ITS EFFECTIVENESS: RELEVANCE OF CREATION AND INTRODUCTION OF NEW ANTI-CRISIS PROGRAMS DURING THE CRISIS - Artem N. Bulavin (Статистика и экономика)
Instability of the market economy, strengthened competition and the global economic crisis which began in 2008 caused aggravation of the situation in the domestic automotive industry. The measures which are being realized by government should be reconsidered and actualized taking into account changed conditions. Also its effectiveness should be improved.